Non-economic losses and other impacts of climate change affecting women in the tourism industry: a photovoice case study from Kenya's coast - Atieno, Lucy (Frontiers in Climate, 2025)
Coastal areas drive much of the world's tourism growth, yet they are highly vulnerable to the impacts of climate change. This vulnerability poses a significant risk to the tourism sector, as environmental degradation can diminish the appeal of destinations. The tourism sector's strong dependence on women's work exposes it to gendered impacts, as climate risks in coastal environments are not gender-neutral but affect women disproportionately. Despite the growing attention to climate change in tourism research, methodological limitations have often overlooked household and community scales, thereby underutilizing women's knowledge and lived experiences. This study addresses these gaps by using photovoice, a participatory method that enables participants to frame and articulate climate-related changes in their own terms, based on their lived experiences. The participants' photovoices revealed changes in natural resources and coastal infrastructure linked to the spaces where women's work takes place and upon which it depends. A feminist political ecology lens informs the interpretation of these results, suggesting that the growing uncertainty associated with climate change has blurred the boundaries of these spaces, which form the core of women's work in tourism, reshaping their roles in ways that reinforce subordination rather than promote equal participation in the ocean economy. Moreover, the photovoices reveal that economic and non-economic losses represent interconnected dimensions of the same processes of change. The interaction between climate change and tourism thus introduces multidimensional, gender-related vulnerabilities that extend beyond economic impacts to include implications for women's political agency and a sense of cultural pride. By focusing on women's experiences, this study enhances our understanding of gendered vulnerabilities in coastal tourism and provides insights for developing more inclusive practices that promote gender equity and diversity in marine environments.